The ethics of consent. (2nd January 2019) - Ellis, Peter
Abstract : As healthcare professionals, we come into contact with patients on a daily basis, and it is important that the professional relationship we develop with our patients is one built on respect and trust. One important element of this is gaining consent. In this article, Peter Ellis explores what consent is, why it is important and when and how it should be gained